The Effect of MSME Credit, PMA and PMDN on Economic Growth and Unemployment in Central Kalimantan Province - Setiani Br Sinulingga (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2021)
This study aims to determine the direct effect of MSME credit, PMA and PMDN on Economic Growth and the indirect effect of MSME, PMA and PMDN credit on Unemployment through Economic Growth in Central Kalimantan Province. The method used to analyze the data in this study is a quantitative analysis method obtained from the Central Statistics Agency (BPS) of Central Kalimantan and Bank Indonesia Central Kalimantan. The data used in this study is panel data, which is a combination of time series data and cross section data. The model used is Path Analysis Model. The results of this study indicate that the direct effect of MSME credit has no significant effect on economic growth, while PMD and PMDN have a significant effect on economic growth. MSME credit and economic growth have a significant effect on unemployment while PMA and PMDN have no significant effect on unemployment. While the indirect effect where PMDN is negatively related has a significant effect on unemployment through economic growth and MSME credit and PMA have no significant effect on budgeting through economic growth.